A binary fuzzy goal programming model with fuzzy parameters to select the fruits and vegetables market hall location for Istanbul - Bilisik, Ozge Nalan; Baracl, Hayri (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In urban areas, delivery of the products necessary to survive to the desired points has vital importance, and public distribution centers (PDCs) are one of the most important components of this system. In this paper, we present a hybrid method to analyze the locations of F&VMHs which is one of the PDCs types. Firstly, the alternative numbers have been decreased by interval-valued trapezoidal fuzzy grey relational analysis (IVTF-GRA) method. Secondly, we develop a binary fuzzy goal programming (BFGP) model with fuzzy parameters to determine the most appropriate F&VMH locations by taking into consideration costs, arrival times and CO2 emission goals. Then, the BFGP model is converted to standard FGP model. In the last stage, the constraints with fuzzy parameters are transformed to crisp constraints with Peidro et al. (2010)'s methodology. The results show that current F&VMHs need to be moved to the locations that are more cost effective and out of the city center.
Keywords: IVTFGRA; BFGP; Fuzzy parameters; Location selection; Public DCs; INTERNATIONAL DISTRIBUTION CENTER; GREY RELATIONAL ANALYSIS; DISTRIBUTION CENTERS; PERISHABLE PRODUCTS; LOGISTICS; OPTIMIZATION; DESIGN; METHODOLOGY; ALLOCATION; ALGORITHM; Computer Science; Engineering; Operations Research & Management Science